Prediction of tunneling induced surface settlement using empirical methods [electronic resource] - Chan, Yien Wei, 1987-, author (2011)
Project Paper (Sarjana Muda Kejuruteraan (Awam - Geoteknik)) - Universiti Teknologi Malaysia, 2011